A Review of Media Addiction Research From 1991 to 2016. (August 2021) - Leung, Louis; Chen, Cheng
In this review study, a descriptive analysis was conducted of the media addiction research published from 1991 to 2016. The search of all academic output published in 13 major scientific and academic databases in 256 journals within the 26-year period yielded 1, 099 Social Sciences Citation Index/Science Citation Index (SSCI/SCI) articles that were relevant to this study. The review was focused on the trends, developmental periods, study domains, themes, research methods, measurement instruments, and research purposes in the field of media addiction. The results show that most previous media addiction research in the study period were conducted from the perspectives of compulsivity and impairment. As a psychiatric disorder and a complex biopsychosocial phenomenon, the findings suggest that future media addiction research should go beyond the predominant perspectives in the prevalence, causes, and consequences of media addiction (59.7%) and extend into the effectiveness of prevention and treatment (only 3.96%) provided in both clinical and nonclinical settings. The review also shows that of the 974 studies using quantitative or mixed methods to examine media addiction, over 30% used Young's Internet Addiction Test and Diagnostic Questionnaire as the two frequently used measurement scales, which means that they were adopted by at least 20 studies in the study period. Furthermore, over 77% of the media addiction studies employed survey and experiment methods. The implications of these findings for future media addiction research and the limitations of the study are discussed.